Effect of Positive Affirmation on Breastfeeding Outcomes among Mothers at Risk of Preeclampsia: A Quasi-Experimental Study - Ahmaniyah; Reni Yuli Astutik (Universitas STRADA Indonesia, 2026)
Background: Preeclampsia is associated with increased risk of breastfeeding difficulties, including delayed lactogenesis and reduced exclusive breastfeeding. Psychological factors may influence breastfeeding outcomes, and simple psychosocial interventions such as positive affirmations may offer potential benefits. Purpose: To evaluate the effectiveness of a positive-affirmation intervention on breastfeeding outcomes among mothers at risk of preeclampsia. Methods: A quasi-experimental study with a non-equivalent control group design was conducted in Sumenep from November 2025 to January 2026. A total of 98 mothers were recruited using purposive sampling and allocated into intervention (n = 49) and control (n = 49) groups. The intervention consisted of positive affirmations delivered for 10 minutes per session, twice weekly for four weeks. Outcomes included early initiation of breastfeeding, onset of lactogenesis, and exclusive breastfeeding at one month postpartum. Data were analyzed using independent t-tests and Chi-square tests. Effect sizes were reported as odds ratios (OR) with 95% confidence intervals (CI), and multivariate logistic regression was performed to control for confounders. Results: The intervention group showed a higher rate of successful early initiation of breastfeeding (77.6% vs 55.1%; OR = 2.82; 95% CI: 1.20–6.62; p = 0.018), earlier onset of lactogenesis (42.3 ± 10.5 vs 50.8 ± 12.1 hours; mean difference = −8.5 hours; 95% CI: −13.2 to −3.8; p = 0.001), and higher exclusive breastfeeding rates at one month postpartum (71.4% vs 51.0%; OR = 2.40; 95% CI: 1.08–5.33; p = 0.038). After adjustment, the intervention remained significantly associated with improved breastfeeding outcomes (adjusted OR = 2.40; 95% CI: 1.10–5.50; p = 0.030). Conclusion: Positive-affirmation intervention is associated with improved breastfeeding outcomes among mothers at risk of preeclampsia. Given its simplicity and feasibility, this intervention may be integrated into postpartum care to support breastfeeding practices in high-risk populations.